The Effectiveness of Using the Google Classroom Platform on the Development of Arabic Language Reading Skills among Third-Grade Students in Al-Karak Directorate of Education - Yazan Saleem Al-Ewesat; Muhammad Ibrahim Al-Ghzewat (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2022)
The study aimed to identify the effect of teaching using the Google Classroom platform on the development of reading skills in the Arabic language among third-grade students in the Directorate of Education in Karak. The study relied on the quasi-experimental approach. Its validity and reliability, and the study sample consisted of (42) male and female students of the third grade at Princess Rahma Bint Al Hassan Basic School in Karak Governorate, divided into two groups that were randomly selected, during the second semester of 2021/2022. The results showed that there were statistically significant differences at a lower level (0.05≥α) in the post-application of the reading skills test, and there were statistically significant differences in performance on the reading skills test between the Google Classroom platform and the regular method in favor of the Google Classroom platform. In light of the results, the study recommended recommendations: including the use of the Google Classroom platform in all subjects of basic school education.